2005
DOI: 10.1063/1.1961040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pentaquarks in constituent quark models: recent developments

Abstract: Abstract. Some recent developments in the study of light and heavy pentaquarks are reviewed, mainly within constituent quark models. Emphasis is made on results obtained in the flavor-spin model where a nearly ideal octet-antidecuplet mixing is obtained. The charmed antisextet is reviewed in the context of an SU(4) classification.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…We find a convergent Operator Product Expansion (OPE) only for the non-strange heavy pentaquark sum rule obtained with an interpolating field composed of two diquarks and one anti-charm quark, that has been previously used by us [34]. The stability of non-strange heavy pentaquark is consistent with the result based on the quark model with flavor spin interaction [25]. We then refine the convergent sum rule by explicitly including the DN two-particle irreducible contribution.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…We find a convergent Operator Product Expansion (OPE) only for the non-strange heavy pentaquark sum rule obtained with an interpolating field composed of two diquarks and one anti-charm quark, that has been previously used by us [34]. The stability of non-strange heavy pentaquark is consistent with the result based on the quark model with flavor spin interaction [25]. We then refine the convergent sum rule by explicitly including the DN two-particle irreducible contribution.…”
Section: Introductionsupporting
confidence: 55%
“…The question is whether such strong diquark structure will survive other non-perturbative QCD dynamics in a multiquark environment and produce a stable pentaquark state. Such questions are being intensively pursued in quark model approaches [24][25][26]. In particular, an important question at hand is whether the net attraction from the diquark correlations in the pentaquark configuration is stronger than that from the corresponding diquark and additional quark-antiquark correlation present when the pentaquark separates into a nucleon and a meson state.…”
Section: Introductionmentioning
confidence: 99%
“…The attraction to form a meson becomes smaller if the s is replaced by either a c or b. Full constituent quark model calculations [19,20] indeed find a possible stable heavy pentaquark baryon. A likely pentaquark structure would be that suggested in Ref.…”
Section: Charmed Pentaquark Baryonsmentioning
confidence: 90%
“…The excitation energy of a diquark in a L = 1 state, ∆E L=1 , can be estimated by approximating the charmed baryon as a sum of a charm quark and a diquark, because the interaction between them is small in the heavy quark limit. Attributing the mass difference between the parity doublet partners of the posi- [19,20,22] and the QCD sum-rules study [23] in which a possible stable heavy pentaquark baryon has been found. For a pair of ud and us diquarks in Θ cs (udusc), they do not have to be in the L = 1 state, and hence there is no additional contribution from the orbital energy [24].…”
Section: Charmed Pentaquark Baryonsmentioning
confidence: 99%